2015
DOI: 10.1007/s00253-015-7173-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic optimization of fed-batch simultaneous saccharification and fermentation at high-solid loading based on enzymatic hydrolysis and dynamic metabolic modeling of Saccharomyces cerevisiae

Abstract: An integrative simultaneous saccharification and fermentation (SSF) modeling is a useful guiding tool for rapid process optimization to meet the techno-economic requirement of industrial-scale lignocellulosic ethanol production. In this work, we have developed the SSF model composing of a metabolic network of a Saccharomyces cerevisiae cell associated with fermentation kinetics and enzyme hydrolysis model to quantitatively capture dynamic responses of yeast cell growth and fermentation during SSF. By using mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…Because they are fitted and validated on varied experimental datasets, kinetic models represent a set of collected information of the substrates, enzyme and their interactions. The model used here was originally developed for hydrolysis of birch [ 9 ], was adapted here for wheat straw, and has recently also been adapted for hydrolysis of corn stover [ 20 ], showing the wide validity and applicability of the model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because they are fitted and validated on varied experimental datasets, kinetic models represent a set of collected information of the substrates, enzyme and their interactions. The model used here was originally developed for hydrolysis of birch [ 9 ], was adapted here for wheat straw, and has recently also been adapted for hydrolysis of corn stover [ 20 ], showing the wide validity and applicability of the model.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of viable yeast cells, measured by colony forming assay, has been found to correlate with the ethanol production during SSF/SSCF of pre-treated birch, spruce and wheat straw, and the viability, estimated as colony forming units (CFU) per total cell count, often decreases during SS(C)F at high gravity [ 9 , 10 , 15 , 21 ]. Feeding cells, in other words, split inoculation, has been shown to effectively improve the viability of the population as well as the ethanol production in 20 % (w/w) WIS SS(C)F on birch, spruce and corn stover [ 9 , 10 , 20 ]. In this work, the effects of cell feeding on SSCF were examined under varied solid feeding schemes.…”
Section: Resultsmentioning
confidence: 99%
“…Only the overall process efficiency obtained in the present study (67%) can still be improved. In order to do that, efforts will Finally, a global analysis of the results obtained in the present study compared to the current literature on ethanol production by SSF in fed-batch mode using different biomass types at high solids content ( [17,31,33,[36][37][38][39] -Table 9) revealed that the strategy proposed here is very promising. As can be seen, Zhao et al [36] and Zhang et al [17] achieved the highest ethanol titers (80.0 and 84.7 g/L) using pre-treated sugarcane bagasse and corncob, respectively.…”
Section: Evaluation Of Fed-batch Strategiesmentioning
confidence: 98%
“…However, the extent of process limitation is dependent on the various factors including the characteristics of biomass, the reactor configuration as well as operational conditions used. In this context, the evaluation of the different configurations of mechanically stirred reactors concomitant to the use of the fed-batch mode has been pointed out as an attractive strategy to overcome the rheological problems observed in SSF process at high biomass loadings [12,[33][34][35].…”
Section: Effect Of Solid Loading In Batch Ssfmentioning
confidence: 99%
“…Carbohydrates in the stillage phase represent wasted resources impacting the overall process yield. Improved processing techniques at the commercial scale including mechanical mixing during solid-phase hydrolysis [34,35], acclimated yeast strains [36,37], and combined solid-and liquid-phase fermentation [7] could reduce the quantity of carbohydrates in the stillage stream. Regardless of carbohydrate recovery, organic matter is the largest fraction of wastewater constituents and should be primary focus of treatment alternatives.…”
Section: Impacts Of Upstream Processes On Wastewater Profile and Altementioning
confidence: 99%